Inspection : a novel - Malerman, Josh (Del Rey, 2019)
"Boys are being trained at one school for geniuses, girls at another. And neither knows the other exists--until now. The innovative author of Bird Box invites you into a tantalizing world of secrets and lies. J is a student at a school deep in a forest far away from the rest of the world. J is one of only twenty-six students, who think of their enigmatic school's founder as their father. His fellow peers are the only family J has ever had. The students are being trained to be prodigies of art, science, and athletics, and their life at the school is all they know--and all they are allowed to know. But J is beginning to suspect that there is something out there, beyond the pines, that the founder does not want him to see, and he's beginning to ask questions. What is the real purpose of this place? Why can the students never leave? And what secrets is their father hiding from them? Meanwhile, on the other side of the forest, in a school very much like J's, a girl named K is asking the same questions. J has never seen a girl, and K has never seen a boy. As K and J work to investigate the secrets of their two strange schools, they come to discover something even more mysterious: each other"--